The Implementation of Soundscape Composition to Identify the Ideal Soundscape for Various Activities - Joko Sarwono; Anugrah Sabdono Sudarsono; Andini Hapsari; Helga Salim; Ranti Dwi Tassia (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Soundscapes are affected by several factors and one of them is the activities done in the space concerned. People expect different acoustic environments for different activities, but there is no specific guidance for designing an ideal acoustic environment for different activities. This study aimed to identify ideal urban acoustic environments for four different activities: reading, relaxing, talking with friends, and playing with children. The ideal acoustic environment was evaluated using the soundscape composition concept. The concept was implemented by an acoustic environment simulator that enabled the respondents to compose their ideal acoustic environment and identify the perception of their composition. The sound source selection and perception rating were analyzed to understand the ideal acoustic environment and perception for different activities. This study identified the ideal soundscapes for four different activities and the perception expected to be present in the ideal environments for those activities. The result can be beneficial as guidance for urban soundscape design.